English Teachers’ Views On Curriculum Transformation In Indonesia - Nurul Hikmah Giawa (Student Research Journal, 2024)
The curriculum is one of the most important parts of the teaching and learning process. Curriculum changes have become an important discussion in the world of education. In Indonesia, there have been eleven curriculum changes. This study aims to analyze English teachers' views on curriculum transformation in Indonesia. Using a qualitative method, this study used a questionnaire as an instrument. This qualitative approach allowed for a comprehensive exploration of the nuanced views and experiences of English teachers. The results of this study show that English teachers have varied perspectives on curriculum change in Indonesia which include the positive impact as well as difficulties encountered. Therefore, support from the government is needed both in maximizing supporting facilities in schools as well as training for teachers